LncRNA TUG1 positively regulates osteoclast differentiation by targeting v-maf musculoaponeurotic fibrosarcoma oncogene homolog B - Ya-jing Du; Qiong-qiong Yu; Xiao-fei Zheng; Su-ping Wang (Taylor & Francis Group, 2020)
Osteoclast differentiation-mediates bone resorption is the key biological basis of orthodontic treatment while the specific mechanism of osteoclastogenesis remains unclear. This study aims to explore the underlying mechanism of the osteoclast differentiation from the perspective of long non-coding RNA (LncRNA). In the present study, the osteoclast differentiation of CD14+ peripheral blood mononuclear cells (PBMCs) was induced by recombinant human macrophage colony-stimulating factor (M-CSF) and receptor activator of nuclear factor κB ligand (RANKL), and LncRNA TUG1 expression was dramatically elevated during this process. Functionally, the silence of TUG1 in CD14+ PBMCs decreased tartrate-resistant acid phosphatase (TRAP)-positive cell numbers and the protein levels of TRAP, nuclear factor of activated T cell c1 (NFATc1), and osteoclast-associated receptor (OSCAR), whereas increased V‐maf musculoaponeurotic fibrosarcoma oncogene homolog B (MafB) protein level. The subsequent experiments confirmed that TUG1 lessened the MafB protein level via accelerating its degradation. Then, the interference of MafB reversed the inhibitory effect of si-TUG1 on osteoclastogenesis, including increased the TRAP-positive cell numbers and up-regulated the protein levels of osteoclast markers. Finally, the in vivo experiments displayed that the increased TUG1 levels could promote tooth movement and bone resorption via facilitating osteoclast differentiation in the rat model of orthodontic tooth movement. In summary, TUG1 overexpressed during the process of osteoclast differentiation and positively regulated osteoclast differentiation by targeting MafB.